Strategi Komunikasi Politik Lis Darmansyah dan Raja Ariza dalam Mendapatkan Dukungan Pemilih Pemula pada Pilkada 2024 - Syaihidina Hefir; Bismar Arianto; Uly Sophia (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study aims to analyze the political communication strategies employed by Lis Darmansyah and Raja Ariza in gaining support from first-time voters during the 2024 Tanjungpinang mayoral election. The research employed a qualitative descriptive method, with data collected through interviews, observations, and documentation. The analysis was conducted using the theoretical framework of political communication strategies integrated with persuasive communication and participatory campaign approaches to examine the effectiveness of political messages delivered to first-time voters. The findings reveal that the success of Lis Darmansyah and Raja Ariza was supported by adaptive communication strategies tailored to the characteristics of young voters. These strategies included humanistic interpersonal communication, balanced utilization of digital and conventional media, and the delivery of simple, relevant, and easily understood political messages aligned with the needs and aspirations of first-time voters. Furthermore, community-based approaches, volunteer involvement, and peer communication patterns effectively fostered emotional connections, strengthened public trust, and encouraged greater political participation. The study concludes that political communication strategies characterized by openness, innovation, consistency, and public participation play a significant role in increasing political support among first-time voters and contributed substantially to the electoral success of Lis Darmansyah and Raja Ariza in the 2024 Tanjungpinang mayoral election.